Retrospective evaluation of laboratory data of patients with telogen effluvium (Annals of Medical Research, 2021)
Aim: Telogen effluvium (TE) is a diffuse non-cicatricial alopecia that is frequently encountered in daily practice. This study aimed to evaluate laboratory data (whole blood count (WBC), iron (Fe), iron binding capacity (TIBC), ferritin, B12 and vitamin D, Zinc (Zn)) of female patients with chronic TE.Material and Methods: One hundred seventy nine female patients who applied to Selçuk University Faculty of Medicine Hospital’s dermatology polyclinic between June 2015 and March 2017 with chronic TE (TE complaint of longer than 6 months) were included in the study.Results: The mean age of the patients was 24±7.4 years. The levels of hemoglobin (HGB) (8.9%) and hematocrit (HCT) (8.9%) , mean corpuscular volume (MCV) (16.2%), Fe (16.8% ) , vitamin B12 (15.1%), Zinc (62%) and vitamin D (68.7%) were lower, TIBC (39.7%) level was higher than the reference range. Conclusion: Although the examinations related to the chronic TE etiology are not clear, we think that laboratory evaluation should be performed for the parameters of vitamin D, B12, Zn and anemia in these patients and the remedy of their deficiencies through supplements may be useful in the treatment.
Keywords: Iron; telogen effluvium; vitamin B12; vitamin D; zinc